Synergistic nanostructured MnOx/TiO2 catalyst for highly selective synthesis of aromatic imines - Sudarsanam, Putla; Kockritz, Angela; Atia, Hanan; Amin, Mohamad Hassan; Bruckner, Angelika (ChemCatChem, 2021)
This work reports the development of a synergistic nanostructured MnOx/TiO2 catalyst, with highly dispersed MnOx nanoparticles (4.5 +/- 1 nm) on shape-controlled TiO2 nanotubes (8-11 nm width and 120-280 nm length), for selective synthesis of valuable aromatic imines at industrially important conditions. Pristine TiO2 nanotubes exhibited 97 % imine selectivity at a 38.3 % benzylamine conversion, whereas very low imine selectivity was obtained over commercial TiO2 materials, indicating the catalytic significance of shape-controlled TiO2 nanotubes. The MnOx nanoparticle/TiO2 nanotube (10 wt% Mn) catalyst calcined at 400 degrees C showed the best activity with 95.6 % benzylamine conversion and 99.9 % imine selectivity. This catalyst exhibited good recyclability for four times and is effective for converting numerous benzylamines into higher yields of imines. The high catalytic performance of MnOx/TiO2 nanotubes was attributed to higher number of redox sites (Mn3+), high dispersion of Mn species, and shape-controlled structure of TiO2, indicating that this catalyst could be a promising candidate for selective oxidation reactions.
Keywords: Acid-redox properties; aerobic oxidation; Nanostructured catalyst; Selective catalysis; Synergistic metal-oxide interaction